The Effect of Service Quality on Customer Satisfaction at PT. Bank Rakyat Indonesia (Persero) Tbk. Tobelo Branch and Its Implications for Service Improvement - Oktadwilaras A P. Papuling; Alfriani Puren (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
The type of research conducted is quantitative. Determination of the research sample uses the Slovin formula for sampling. Research data was obtained by distributing questionnaires about service quality and customer satisfaction to 45 respondents using a Likert scale. It can be seen that service quality is a very important factor in ensuring customer satisfaction. Based on the concept of marketing and service management, service quality has a positive and significant effect on customer satisfaction, meaning that the better the quality of service provided by BRI Tobelo Branch (seen from the speed of service, friendliness of officers, accuracy of transactions, adequate facilities, and ease of access), the higher the level of customer satisfaction. On the other hand, a decrease in service quality will decrease customer satisfaction. Based on these positive influences, the implications are: Standardization of Service SOPs ensures that all frontliners have consistent service standards, Improving Employee Competence through communication training, complaint handling, and bank product literacy, Optimization of Physical & Digital Facilities improves the comfort of waiting rooms, speeds up queues, and improves the quality of e-banking services, Implementation of a Feedback System regularly measures customer satisfaction to detect areas that need improvement, Strengthening the Culture of Excellent Service builds the mindset of all employees that customer satisfaction is the main priority.